2021
DOI: 10.1016/j.biochi.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

EGCG as an anti-SARS-CoV-2 agent: Preventive versus therapeutic potential against original and mutant virus

Abstract: In the search for anti-SARS-CoV-2 drugs, much attention is given to safe and widely available native compounds. The green tea component epigallocatechin 3 gallate (EGCG) is particularly promising because it reportedly inhibits viral replication and viral entry in vitro . However, conclusive evidence for its predominant activity is needed. We tested EGCG effects on the native virus isolated from COVID-19 patients in two independent series of experiments using VERO cells and two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…It has also been shown in vitro that EGCG treatment decreased 3CL-protease activity of HCoV-OC43 and HCoV-229E, as well as HCoV-OC43-induced cytotoxicity ( Liu et al, 2021b , Jang et al, 2021 ). Other studies have shown that EGCG effectively blocks infection of SARS-CoV-2 and new variants by inhibiting spike binding to ACE2 receptor ( Joseph et al, 2021 ; Liu et al, 2021a ) and EGCG has been suggested for prevention COVID-19 ( Tsvetkov et al, 2021 ). It was also shown, that EGCG blocks not only the entry of SARS-CoV-2, but also MERS- and SARS-CoV pseudo-typed lentiviral vectors and inhibited virus infections in vitro ( Henss et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown in vitro that EGCG treatment decreased 3CL-protease activity of HCoV-OC43 and HCoV-229E, as well as HCoV-OC43-induced cytotoxicity ( Liu et al, 2021b , Jang et al, 2021 ). Other studies have shown that EGCG effectively blocks infection of SARS-CoV-2 and new variants by inhibiting spike binding to ACE2 receptor ( Joseph et al, 2021 ; Liu et al, 2021a ) and EGCG has been suggested for prevention COVID-19 ( Tsvetkov et al, 2021 ). It was also shown, that EGCG blocks not only the entry of SARS-CoV-2, but also MERS- and SARS-CoV pseudo-typed lentiviral vectors and inhibited virus infections in vitro ( Henss et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… The IC 50 of EGCG for CPE was 5.0 μM and CPE was almost fully inhibited by EGCG at the doses of 25 and 50 μM. Tsvetkov et al (2021) Partial EGCG treatment in which SARS-CoV-2 was pre-incubated with EGCG prior to the infection. The IC 50 of EGCG for CPE was 0.6 μM.…”
Section: Antiviral Activity Of Egcg Against Sars-cov-2mentioning
confidence: 98%
“… The IC 50 of EGCG for plaque formation was 4.0 μM and the plaque formation was highly inhibited by EGCG at a dose of 20 μM. Tsvetkov et al (2021) Partial EGCG treatment in which SARS-CoV-2 was pre-incubated with EGCG prior to the infection and EGCG was added to cells after infection. The IC 50 of EGCG for plaque formation was 3.8 μM and the plaque formation was fully inhibited by EGCG at a dose of 44 μM, which did not cause cytotoxicity after a 48-h incubation.…”
Section: Antiviral Activity Of Egcg Against Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG, previously mentioned as a potential M pro inhibitor, has also been shown to interact with viral S protein subunits, including S2 and RBD domains of both original and UK strain mutant virus, thus interrupting interaction with ACE2. EGCG binds to the RBD domain of the UK strain mutant slightly more effectively [115].…”
Section: S Protein and S-ace2 As A Targetmentioning
confidence: 99%